IMPLEMENTASI AKTIVITAS STIMULASI MOTORIK HALUS BERBASIS BERMAIN PADA BALITA DI POSYANDU BUNGA TANJUNG - Al Um Aniswatun Khasanah; Nabila Nur Afifah Fitri; Efraldo Yudistira; Muhammad Tasa Kasumbang; Muhammad Faris Nuuruddin; Bota Muhammad Akbar (Journal of Hospital Administration and Excellent Health Service, 2026)
Introduction: Fine motor development is a crucial aspect of child growth and development that should be stimulated early through play activities appropriate to the child's developmental stage. Posyandu (Integrated Health Service Posts) have the potential to serve as promotive and preventive community-based health services for providing developmental stimulation. This study aimed to describe the implementation of play-based fine motor stimulation activities for toddlers at Posyandu Bunga Tanjung. Methods: This study employed a descriptive observational design with a cross-sectional approach. The participants were all toddlers who attended the fine motor stimulation activities at Posyandu Bunga Tanjung on April 18, 2026, selected using a total sampling technique. The stimulation activities included color matching games, a marble maze, puzzles, and a ball relay using bottle caps. Data were collected through direct observation and analyzed descriptively using frequency distributions and percentages. Results: A total of 49 toddler participations were recorded, consisting of color matching games (n=22), marble maze (n=13), puzzles (n=8), and ball relay (n=6). The color matching games showed the greatest variation in repetition frequency, whereas the other three activities were predominantly completed with a single repetition. Conclusion: Play-based fine motor stimulation activities can be implemented in Posyandu as a promotive strategy to stimulate various components of fine motor skills according to the characteristics of each activity. The variation in repetition frequency reflects toddlers' participation patterns during the activities rather than the effectiveness of the intervention or improvements in fine motor skills.